2010
DOI: 10.1186/cc8885
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption is depressed in patients with lactic acidosis due to biguanide intoxication

Abstract: IntroductionLactic acidosis can develop during biguanide (metformin and phenformin) intoxication, possibly as a consequence of mitochondrial dysfunction. To verify this hypothesis, we investigated whether body oxygen consumption (VO2), that primarily depends on mitochondrial respiration, is depressed in patients with biguanide intoxication.MethodsMulticentre retrospective analysis of data collected from 24 patients with lactic acidosis (pH 6.93 ± 0.20; lactate 18 ± 6 mM at hospital admission) due to metformin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 39 publications
6
55
0
3
Order By: Relevance
“…Principle mechanism of MALA is thought to be inhibition of mitochondrial function in hepatocytes resulting in inhibition of aerobic oxidation and accumulation of lactate [13]. This explains why haemodiafiltration is effective in treatment as it removes metformin and lactate to negate acidosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Principle mechanism of MALA is thought to be inhibition of mitochondrial function in hepatocytes resulting in inhibition of aerobic oxidation and accumulation of lactate [13]. This explains why haemodiafiltration is effective in treatment as it removes metformin and lactate to negate acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Infact in some case series survivors have had higher lactate levels [30]. This is probably due to the fact that mitochondrial inhibition by metformin is easily reversed by haemodialysis irrespective of the pH or lactate level which are rapidly reversible [13]. Furthermore, reviewing recent literature Renda et al postulate that associated co-morbid risk factors are stronger predictors of mortality than the dose of metformin or degree of impairment of its elimination, in metformin intoxication [5].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis is partially affected by host factors and comorbidities such as renal failure, hypoxia, and hypotension. 6 Since MALA is associated with high mortality, early recognition and stoppage of drug is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…We consider that lactate clearance determination may be a better prognostic factor of organic failure and mortality, because patients with high lactate clearance have less mortality rate than those with low lactate clearance. The best lactate clearance rate is correlated as well with decreased in some biomarker such as interleukins 1,6,8,10, tumor necrosis factor alpha, caspase 3. On the other hand, some studies have demonstrated that normal lactate rates can be found on cardiogenic shock, acute renal failure, and that lactate clearance are altered on these, probably because of multiorgan failure (9,(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 89%
“…Lactate production is not only originated by anaerobic metabolism, but by mediators of inflammatory response, catecholamine's, endotoxins 2,3 and decreased of lactate clearance by the liver (8)(9)(10). Elevated seric lactate concentrations are found in hepatic cirrhosis, renal failure, diabetes mellitus, cancer, convulsions, cholera, acute pancreatitis and use of pharmaceutics (biguanides, isoniazide, nitroprusiate, ethanol, salicylates, lactulose, etc.)…”
Section: Introductionmentioning
confidence: 99%